AUTHORITY vs. ENGAGEMENT: DYNAMICS OF YOUNG MILLENNIAL PARENTS: OTORITAS vs KETERLIBATAN: DINAMIKA ORANG TUA MUDA MILINEAL - Nurhayati (EDUCATE, 2024)
Young millennial parents face unique challenges in meeting the demands of parenting in the digital era. This research aims to explore the dynamics between authority and involvement in young millennial parents' awareness of child care. Data were analyzed using the multiple regression method to measure the influence of each independent variable on the dependent variable, with correlation data that had been obtained previously. The strength of the correlation was measured using the Pearson correlation coefficient. The findings showed that young millennial parents showed a correlation value (r) between the overall independent variable and the dependent variable of 0.789. In conclusion, the significant relationship between several independent variables and the dependent variable (Long Term Impact) shows the important role of communication, participation and negotiation in children's development. These findings provide new insights into understanding the factors that influence long-term child development.